Determination of T-lymphocyte subsets in bronchoalveolar lavage of patients with pulmonary sarcoidosis - Petrek, M; Kolek, V (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1991)
Bronchoalveolar T-lymphocyte subsets were evaluated in seven patients with pulmonary sarcoidosis and eight patients with other interstitial lung disorders. Both disease groups considerably differed in the distribution of bronchoalveolar CD4+ and CD8+ cells. The lymphocytic alveolitis in sarcoidosis was characterized by excess CD4+ (helper-inducer) cells; mean CD4/CD8 ratio was 6.8 +/- 3.8. Inversely, in the lungs of patients with other interstitial pulmonary disorders a less pronounced but clear predominance of CD8+ (suppressor-cytotoxic) lymphocytes was observed with CD4/CD8 ratio 0.7 +/- 0.4. The results of the study suggest that the determination of the major immunoregulatory subsets of bronchoalveolar lymphocytes contributes to the reliable differentiation of sarcoidosis from other interstitial lung disorders. The recent advances improving our understanding of the pathogenesis of sarcoidosis are briefly reviewed in the discussion.
Keywords: senioři; lidé; plicní nemoci; Middle Aged; mužské pohlaví; Adult; bronchoalveolární lavážní tekutina; Lung Diseases; ženské pohlaví; Humans; sarkoidóza; Bronchoalveolar Lavage Fluid; lidé středního věku; T-Lymphocyte Subsets; dospělí; Female; Aged; T-lymfocyty - podskupiny; Sarcoidosis; Male